VERBA TAKTRANSITIF BAHASA MANGGARAI DIALEK RAHONG OLEH MAHASISWA MANGGARAI DI YOGYAKARTA - Agustinus L.T. Jemparut; Nusarini Nusarini (CARAKA, 2015)
The aims of this research are describing (1) the intransitive verb patterns in Rahong - Manggarai Dialect, (2) the intransitive verb types in Rahong - Manggarai Dialect, and (3) the intransitive verb meaning in Rahong - Manggarai Dialect.This research applied descriptive qualitative research. The Data were sentences containing verbs /the intransitive verb in Manggaraidialect. The data sources were Manggarai language used by The West Manggarai studentsâ€Ÿ family association (Keluarga Besar Mahasiswa Manggarai Barat). The data collection technique used observation method and its continual method: observation involves a free interview. The data analysis technique was pair-sort technique as a determiner, translational sorting another language as a determiner, and apportion method which using deletion technique. The result data presentation method used the informal method.The research results are (1) the intransitive verb patterns used by students were: (a) infinitive intransitive verbs, (b) affix intransitive verbs. (2) Types â€“ the intransitive verb types: (a) the intransitive complement verbs, (b) the intransitive- obligatory complement verbs, (c) the optional intransitive verbs. (3)The intransitive verb meanings are (a) inherent action meaning, (b) inherent process meaning, (c) inherent situational meaning.Â